Death by sex in an Australian icon: a continent‐wide survey reveals extensive hybridization between dingoes and domestic dogs. Issue 22 (6th November 2015) - Stephens, Danielle; Wilton, Alan N.; Fleming, Peter J.S.; Berry, Oliver
Abstract: Hybridization between domesticated animals and their wild counterparts can disrupt adaptive gene combinations, reduce genetic diversity, extinguish wild populations and change ecosystem function. The dingo is a free‐ranging dog that is an iconic apex predator and distributed throughout most of mainland Australia. Dingoes readily hybridize with domestic dogs, and in many Australian jurisdictions, distinct management strategies are dictated by hybrid status. Yet, the magnitude and spatial extent of domestic dog–dingo hybridization is poorly characterized. To address this, we performed a continent‐wide analysis of hybridization throughout Australia based on 24 locus microsatellite DNA genotypes from 3637 free‐ranging dogs. Although 46% of all free‐ranging dogs were classified as pure dingoes, all regions exhibited some hybridization, and the magnitude varied substantially. The southeast of Australia was highly admixed, with 99% of animals being hybrids or feral domestic dogs, whereas only 13% of the animals from remote central Australia were hybrids. Almost all free‐ranging dogs had some dingo ancestry, indicating that domestic dogs could have poor survivorship in nonurban Australian environments. Overall, wild pure dingoes remain the dominant predator over most of Australia, but the speed and extent to which hybridization has occurred in the approximately 220 years since the first introduction of domestic dogs indicate that the process may soon threaten the persistence of pure dingoes.